5-HT Inhibits Calcium Current and Synaptic Transmission from Sensory Neurons in Lamprey - El Manira, Abdeljabbar (J Neurosci, 1997)
In the lamprey spinal cord, 5-hydroxytryptamine (5-HT) immunoreactivity (ir) is present in the ventromedial plexus originating from intraspinal neurons, ventrolateral column arising from the brainstem, and dorsal column. The latter 5-HT system originates from small dorsal root ganglion neurons. Combined Lucifer yellow intracellular labeling of the intraspinal sensory neurons, dorsal cells, and 5-HT immunohistochemistry showed close appositions between 5-HT-ir fibers and dorsal cell axons. Application of 5-HT depressed monosynaptic EPSPs evoked in giant interneurons by stimulation of single dorsal cells, dorsal roots, or dorsal column without any detectable change in the input resistance of postsynaptic neurons. Furthermore, the amplitude of AMPA-evoked depolarizations in giant interneurons was unaffected by 5-HT. The lack of postsynaptic effects of 5-HT indicates that the decrease of the amplitude of sensory monosynaptic EPSPs by 5-HT is mediated by presynaptic mechanisms. The inhibition of monosynaptic EPSPs by 5-HT was not counteracted by an antagonist of 5-HT(1A) receptors. 5-HT also reduced the amplitude of the calcium current recorded in isolated dorsal cells and slowed down its kinetics. The inhibition of calcium channels could represent the mechanism mediating the depression of synaptic transmission at the axonal level. These results show that activation of 5-HT receptors on dorsal cell axons as well as on other sensory neurons mediates inhibition of sensory synaptic transmission to giant interneurons. In intact animals, 5-HT could be released from small 5-HT neurons in dorsal root ganglia, which thus may underlie direct sensory–sensory interactions.